EMPLOYEE PERFORMANCE IN THE GENERAL SECTION OF THE REGIONAL SECRETARIAT OF SUKOHARJO REGENCY - Zaman, Farouq Syaiful; Istiatin, Istiatin; Sarsono, Sarsono (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2025)
This study was used to see the influence of motivation, competence, leadership style, and human resource management on Employee Performance in the General Section of the Regional Secretariat of Sukoharjo Regency. This study used a quantitative descriptive approach with data collection using questionnaires, observations, documentation, interviews and literature studies. The research was conducted at the General Section Office of the Regional Secretariat of Sukoharjo Regency located in the Wijaya Tower Building. This research was conducted for 6 months. The population in this study were 40 employees of the General Section of the Regional Secretariat of Sukoharjo Regency. This study will use a non-probability sampling approach. The sample taken in this study was 40 employees of the General Section of the Regional Secretariat of Sukoharjo Regency. This study uses a linear regression analysis tool with the help of SPSS software. Based on the results of hypothesis testing and the discussion that has been carried out, it can be concluded that Motivation, Competence, Leadership Style, Human Resource Management have a significant effect on employee performance in the General Section of the Regional Secretariat of Sukoharjo Regency.